La Guadeloupe, une prison à ciel ouvert dans : Cent vies et des poussières de Gisèle Pineau - Noura Hamouche (Multilinguales)
The aim of this article is to try to see how the confinement of the physical world extends to the mental structure of the characters in Hundred Lives and Dust through the exclusion grids of Michel Foucault’s discourse. We will discuss the author’s writing processes through the external exclusion procedures proposed by the French philosopher. We will also see how the Foucauldian principle of heterotopias can serve as an analytical tool to express the perdition of the Black people of Guadeloupe under the sign of slavery that seems to endure without saying its name. Likewise, the work of Franz Fanon in psychiatry who names forms of identity alienation among blacks, as well as the ethnological work of Stéphanie Mulot on the West Indian communities and their family and social specificities, inherited from centuries of slavery, we will serve points of support for a description and interpretation as close as possible to the text and its cultural content.